Housing market regulation has contributed to the worldwide triumph of home ownership - Konstantin Cholodilin; Sebastian Kohl (DIW Weekly Report, 2019)
The present report presents new historical data based on country comparisons and research results regarding rent control and its long-term effect on the home ownership rate in 27 countries. Policy measures of rent control, protection against eviction, and housing space management have been widespread in most of the countries studied-particularly in continental Europe-in the past 100 years. At the same time, the rate of home ownership in those countries has steadily risen in the long term. The present analysis shows that in the past century, the triumph of home ownership has not only been the result of relevant incentive measures and financial market liberalization. Indirectly, it is also due to rent control.
Keywords: C23; O18; R38; 330; tenancy regulation; homeownership; crowding-out